Salinity tolerance of five ornamental species from the Asteraceae family in seed germination and early seedling growth stages - Maryam Davoudi; Hassan Bayat (Journal of Horticulture and Postharvest Research, 2024)
Purpose: Seed germination and seedling growth are recognized as the most sensitive stages of salinity for the majority of plant species. This experiment aimed to characterize the impact of various salinity levels on selected ornamental plants from the Asteraceae family including Gazannia splendens, Rudbeckia hirta, Ageratum houstonianum, Gaillardia aristata, and Coreopsis grandiflora during the seed germination stage. Research method: Five independent experiments were conducted in a completely randomized design (CRD), comprising seven treatments with different concentrations of sodium chloride (0, 20, 40, 60, 80, 100, and 120 mM) in four replications using Petrie plates. Findings: The salinity of 120 mM significantly reduced the seed germination percentage in G. splendens, G. aristata, and C. grandiflora, compared to the other species. A. houstanianum exhibited a stimulating effect on seed germination percentage with salinity levels ranging from 20 mM to 80 mM. Salinity stress at a concentration of 120 mM had negatively affected vegetative traits in A. houstonianum, R. hirta, G. aristata, and C. grandiflora, inhibiting the growth of plumule in A. houstonianum and C. grandiflora. However, traits like plumule length and seedling length in G. splendens remained unaffected by salinity. Research limitations: No limitations were identified. Originality/Value: Results demonstrate varied responses of ornamental plants to different salinity levels. R. hirta exhibited superior performance in seed germination and early seedling stages compared to other plants.